2016
DOI: 10.3747/co.23.2775
|View full text |Cite
|
Sign up to set email alerts
|

Expression of APPL1 Is Correlated with Clinicopathologic Characteristics and Poor prognosis in Patients with Gastric Cancer

Abstract: Background Although appl1 is overexpressed in many cancers, its status in gastric cancer (gc) is not known. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, this finding was different from a few studies, which found that APPL1 was highly expressed in cholangiocarcinoma (CHOL), liver hepatocellular carcinoma (LIHC), stomach adenocarcinoma (STAD), and breast cancer. Ding Oxidative Medicine and Cellular Longevity that the expression of APPL1 was upregulated in breast cancer (MCF-7) and liver cancer cells (HepG2), and they verified that APPL1 could promote the proliferation and migration of tumor cells via leptin-mediated phosphorylation of STAT3, ERK1/2, and AKT, which could explain the relevant mechanisms [31][32][33]. The clinical prognosis analysis for KIRC showed that the survival rate was significantly lower in an APPL1-downregulated condition (Figure 3).…”
Section: Discussionmentioning
confidence: 86%
“…However, this finding was different from a few studies, which found that APPL1 was highly expressed in cholangiocarcinoma (CHOL), liver hepatocellular carcinoma (LIHC), stomach adenocarcinoma (STAD), and breast cancer. Ding Oxidative Medicine and Cellular Longevity that the expression of APPL1 was upregulated in breast cancer (MCF-7) and liver cancer cells (HepG2), and they verified that APPL1 could promote the proliferation and migration of tumor cells via leptin-mediated phosphorylation of STAT3, ERK1/2, and AKT, which could explain the relevant mechanisms [31][32][33]. The clinical prognosis analysis for KIRC showed that the survival rate was significantly lower in an APPL1-downregulated condition (Figure 3).…”
Section: Discussionmentioning
confidence: 86%
“…The majority of other genes identified in the current study have also been reported to be involved in various types of cancer and diseases. These include ABCB7 in myelodysplastic syndromes (31), SFMBT1 in cervical cancer (32), and APPL1 in gastric cancer (33,34). These results may provide helpful evidence for further research into breast cancer.…”
Section: Discussionmentioning
confidence: 89%
“…S3G). Among these genes, higher expression of C3AR1 , FCER1G , and AAPL1 has been previously linked to an unfavorable prognosis in ESCC patients [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%